Electrocardiographic changes in Chronic Obstructive Pulmonary Disease patients with elevated Pulmonary Artery Systolic Pressure - Humagain, S; Keshari, S; Gurung, R; Pant, P; Pokharel, B; Koju, R; Bedi, TRS (Nepalese Heart Journal, 2013)
Background Chronic Obstructive Pulmonary Disease (COPD) is a common global problem and most common medical problem in Nepal having significant morbidity and mortality. One of the pathogenesis of COPD in long run is the elevation of Pulmonary Artery Systolic Pressure (PASP) leading to right heart failure. A simple investigation - an Electrocardiograph (ECG) is assessed to co-relate with elevated PASP measured by Echocardiography in COPD patients of Dhulikhel Hospital. Methods and Materials A retrospective case control study of 342 COPD patients was done with assessment of ECG to co-relate with elevated PASP and with normal PASP. Data were analyzed using SPSS 17. Result There was significant difference in mean age, P amplitude in Lead II, III and aVF, QRS axis and R wave in V1 and S in V6 between two groups. Conclusion ECG changes are fairly sensitive and specific for elevation of PASP. DOI: http://dx.doi.org/10.3126/njh.v8i1.8330 Nepalese Heart Journal Vol.8(1) 2011 pp.12-15